Impact of resilience, social support, and perceived health status on happiness among nursing students: A cross-sectional study - Nguyen Ngoc Quynh Nga; Diep Thi Tieu Mai; Pham Thi Thuy; Tran Thi Tuyet Linh (Nursing Practice Today, 2025)
Background & Aim: Happiness is essential for the success of nursing students, but it is often challenged by academic, clinical, and personal stressors. The COVID-19 pandemic further disrupted nursing education, adversely affecting mental health and potentially impacting students’ happiness. This study aimed to examine factors influencing nursing students’ happiness in the post-pandemic era to inform interventions for improved well-being and future success. Methods & Materials: A cross-sectional study was conducted on 250 full-time nursing students at a university in Vietnam. A proportional sampling method was applied. The Brief Resilience Scale, Multidimensional Scale of Perceived Social Support, and Oxford Happiness Questionnaire were used to assess participants’ resilience, social support, and happiness, respectively. The ANOVA test, Pearson's correlation coefficient, and multiple linear regression were employed to analyze data with a p-value less than 0.05. Results: The mean happiness score of nursing students was 3.99 (SD=0.51) out of 6. Reason for enrolling in nursing (p=0.021), satisfaction with the nursing field (p<0.001), perceived health status (p<0.001), resilience (r=0.493, p<0.001), and social support (r=0.628, p<0.001) were related to happiness. Perceived health status (β=-0.214, t=-0.214, p<0.001), resilience (β=0.322, t=7.373, p<0.001), and support from family (β=0.361, t=5.316, p<0.001) were predictors of happiness. Conclusion: The study revealed a moderate level of happiness among nursing students in the post-pandemic era. Key determinants of happiness included perceived health status, resilience, and family support. These findings emphasize the importance of institutions to prioritize interventions aimed at enhancing resilience, promoting healthy lifestyles, and strengthening family support systems.